2020
DOI: 10.1111/bjc.12267
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in avoidance and repetitive negative thinking following symptom provocation in men and women with spider phobia

Abstract: Objectives. Women's greater prevalence of anxiety disorders compared to men is widely assumed to be partly due to gender differences in cognitive and behavioural factors that perpetuate anxiety, such as repetitive negative thinking (RNT) and avoidance. However, past studies assessing this assumption have not controlled for gender differences in baseline symptom severity, the type of stressful life experiences against which RNT and avoidance are measured, or emotional reactivity to these experiences. Design. Us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
2
4
0
Order By: Relevance
“…This held true for ratings in both fear and disgust (see Fig 4 ). Although these results are generally in line with results of other researchers (negative emotions elicited by spiders [ 21 , 32 , 58 , 60 , 99 101 ]; gender differences [ 102 ]), two interesting points can be discussed.…”
Section: Discussionsupporting
confidence: 90%
“…This held true for ratings in both fear and disgust (see Fig 4 ). Although these results are generally in line with results of other researchers (negative emotions elicited by spiders [ 21 , 32 , 58 , 60 , 99 101 ]; gender differences [ 102 ]), two interesting points can be discussed.…”
Section: Discussionsupporting
confidence: 90%
“…Exploring gender differences related to C-19ASS, the findings of the present study showed that females had higher levels of C-19ASS-Avoidance than males. An explanation for this result may lie with previous results, which showed that females are more likely to engage in heightened avoidance than males (Graham et al, 2020). This finding is consistent with previous evidence suggesting that females may show more severe COVID-19 anxiety syndrome than males (Akbari et al, 2022;Mansueto et al, 2022).…”
Section: Construct Validity Invariance Across Gender Groups Internal ...supporting
confidence: 91%
“…This gender distribution is unsurprising given the higher prevalence of anxiety disorders and spider fear among women (Arrindell, 2000;McLean & Anderson, 2009). However, the gender imbalance may limit the generalizability of our results to the general population, which is supported by evidence for different response patterns in men and women (Graham et al, 2020). Moreover, our sample consisted of mostly White individuals, further limiting the generalizability to different ethnicities (we do, e.g., not know if the Caucasian hand displayed in vBATon would influence the perceptions of individuals with different ethnicities; in future versions of vBATon, an option to change the skin tone of the hand may be a worthwhile addition).…”
Section: Limitations and Constraints On Generalitymentioning
confidence: 73%